A biofloc system avoids the adverse effects of diets with suboptimal protein levels on zootechnical performance, intestinal histomorphometry, and protein metabolism of Nile tilapia juvenile fed Spirulina biomass (Arthrospira platensis) as an alternative protein source - Picoli F.* (2024)
© The Author(s), under exclusive licence to Springer Nature B.V. 2024.This study aimed to evaluate the effect of the biofloc technology (BFT) system and the replacement of fish meal with Spirulina biomass on productive performance, intestinal histomorphometry, plasma biochemistry, and oxidative stress of Nile tilapia juveniles (Oreochromis niloticus) fed suboptimal levels of protein. Two factors were evaluated: production systems (clear water × BFT) and replacement of fish meal with Spirulina (0, 33, 66 e 100%). The design was in a 2 × 4 randomized factorial scheme with four replications, and the fish were evaluated for 48 days. Four isoproteic (28% crude protein) diets were formulated with gross energy values close to 4300 kcal kg−1. Nile tilapia juveniles (0.23 ± 0.01 g) were distributed in 16 circular tanks (70 L) at seven fish/tank. The diets were formulated with protein levels approximately 20% below that required for the species and life stage. No interaction was observed between the factors evaluated (production systems × Spirulina inclusion). Rearing the fish in the BFT system avoided the adverse effects of diets with suboptimal protein levels on performance, intestinal histomorphometry, and protein metabolism. Lower values lower lipid peroxidation and higher antioxidant capacity were observed in fish reared in the BFT system, showing evidence of improvements in antioxidant responses and lower levels of physiological oxidative stress. Spirulina completely replaced fish meal in the diets of Nile tilapia juveniles without adverse effects on intestinal morphometry, protein metabolism, and antioxidant response. Replacing 66% of fish meal with Spirulina improved the productive performance, regardless of the rearing system.